Gender Differences and Work-Family Conflicts among Emergency Physicians with Intention to Leave - Wu, Yi-Fang; Wang, Po-Chang; Chen, Yi-Chuan (Emergency Medicine International, 2018)
Backgrounds. The objective of this study was to investigate the relationships among intention to leave, emergency physician clinical activities, work-family conflicts, and gender differences in emergency physicians (EPs). Methods. The survey instrument was a self-administered questionnaire containing basic demographic information and characteristics of clinical activities. The work-family conflicts were assessed by the Chinese version of the work-family conflict (WIF) scale. The questionnaires were mailed to board-certified EPs between January 2014 and August 2014. Student’s t-test, Chi-square test, and one-way analysis of variance (ANOVA) were used to test the difference between subgroups. Logistic regression analysis was performed to determine the factors associated with intention to leave and gender differences. Results. The study included 222 respondents for analysis after exclusions. Compared with physicians not planning to leave, those planning to leave ED practice showed higher dissatisfaction with their clinical work hours (50.0% versus 31.4%, p = 0.035) and night/day shift ratio (52.9% versus 31.0%, p = 0.013) and tended to work with night/day shift ratio exceeding 40% (67.6% versus 45.7%, p = 0.019). Female physicians were more likely to leave ED practice (females versus males, 26.5% versus 10.1%, p = 0.008). A significantly higher level of WIF scale was noted in the group with intention to leave ED practice (3.7 ± 0.6 versus 3.3 ± 0.7, p = 0.001). Conclusions. Females and EPs with higher level of WIF scale were more likely to leave emergency clinical practice. Instead of the number of clinical practice hours, the satisfaction with the clinical work hours and night shift frequency were significantly associated with the intention to leave.